Single-Cell Profiling of Tumor Microenvironment Heterogeneity in Osteosarcoma Identifies a Highly Invasive Subcluster for Predicting Prognosis - Guo, Junfeng; Tang, Hong; Huang, Pan; Guo, Junfeng; Shi, Youxing; Yuan, Chengsong; Liang, Taotao; Tang, Kanglai (Frontiers in Oncology, 2022)
Osteosarcoma is the most common malignant bone tumor in adolescents, and metastasis is the key reason for the treatment failure and poor prognosis in osteosarcoma. Once metastasis occurs, the 5-year survival rate is only approximately 20%, and assessing and predicting the risk of osteosarcoma metastasis are still difficult tasks. In this study, through comprehensive analysis of osteosarcoma single-cell RNA sequencing (scRNA-seq) and bulk RNA-seq data, cellular communication between tumor cells and nontumor cells was identified, illustrating the complex regulatory network in the osteosarcoma microenvironment. In line with the heterogeneity of osteosarcoma, we found subpopulations of osteosarcoma cells that highly expressed COL6A1, COL6A3 and MIF and were closely associated with lung metastasis. Then, BCDEG, a reliable risk regression model that could accurately assess the metastasis risk and prognosis of patients, was established, providing a new strategy for the diagnosis and treatment of osteosarcoma.